ANALISIS PENGENDALIAN KOMUNIKASI DALAM PERENCANAAN PROGRAM DAN ANGGARAN - Yohanes Museng Ola Buluamang (Universitas Mercu Buana, 2023)
In planning development programs and budgets, internal communication control is an important stage to produce proper planning. The purpose of this research is to explore the control of communication in development planning. The research method used is qualitative with a case study approach in the scope of the East Nusa Tenggara provincial government. through descriptive and explanatory analysis, the results of the study reveal three problems of internal communication control that occur in program planning and budgeting. These three communication control problems are related to the existence of an external communication network that is formed in influencing internal communication control. The communication control problem has not been addressed with the resulting communication policy. Therefore, the solution that can be taken is a normative and situational communication policy approach.